2014
DOI: 10.1155/2014/721731
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Abrasion Behaviour of PA 66 Gears in Different Cycles

Abstract: Gears made of plastic-based materials are anticorrosive, resistant to magnetic environments, and light and have pulse decay, low noise, and self-lubrication properties, and therefore their usage areas are widening every single day. In this experiment, the working conditions of 30% fibreglass PA 66 (PA 66 GFR 30) plastic material with PA 66 (PA 66 GFR 30) plastic material and AISI 8620 couple gear are observed. Usage of PA 66 GFR 30 material as gear material at 56.75 Nm constant load and 750 rpm, 1000 rpm, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Therefore, PC/ABS blends are one of the most widely used thermoplastics for automotive, electronic and telecommunication applications. Yakut et al [6] reported that PC/ABS blends could be widely used as gear materials in an open and high moisture environment, since the PC/ ABS materials were durable against flame, air, ultraviolet light, and holding low moisture. Although the mechanical properties of PC/ABS blends, such as tensile strength, fracture toughness etc.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PC/ABS blends are one of the most widely used thermoplastics for automotive, electronic and telecommunication applications. Yakut et al [6] reported that PC/ABS blends could be widely used as gear materials in an open and high moisture environment, since the PC/ ABS materials were durable against flame, air, ultraviolet light, and holding low moisture. Although the mechanical properties of PC/ABS blends, such as tensile strength, fracture toughness etc.…”
Section: Introductionmentioning
confidence: 99%
“…Yakut [1] design gear fatigue test for PA 66 with fiber glass plastic material. To acquire ideal working conditions with plastic-type gears, tooth load and cycle period must be selected appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, permanent viscoelastic/viscoplastic strain accumulation (v) can also occur at higher loads, as identified on steel/PA66 pairs by Sarita et al [5] and on POM/PA66 pairs by Pogac ˇnik et al [7]. At very high loads, polymer gears can additionally experience (vi) fracture at the pitch line (PA66/PA66 gears tested by Mao et al [9]) and melting due to high thermal loads (identified on PA66-GF/PA66-GF pairs analysed by Yakut et al [10] and on a steel/PEEK pair by Lu et al [11]). A concise overview of the expected failure modes of polymer gears and a comprehensive design method for optimizing these components was presented by Tavc ˇar et al [12].…”
mentioning
confidence: 96%